Interaksi Pelanggan Warkop di Jalan Bawakaraeng Sinjai - Dani Saputra (Rayhan Intermedia, 2019)
This study aims to determine the phenomenon of the proliferation of coffee shops showing a shift in people's behavior. The visitors' interest in coffee shops does not necessarily arise from the taste and aroma of coffee served. But for loyal visitors to the coffee shop, keep or make a coffee shop as one of the daily activities that also have an important role in everyday life. This study aims to determine the customer interaction of the parking lot on Jalan Bawakaraeng, Sinjai Regency. The type of research used is descriptive qualitative research with a total of 10 informants. The results showed that the social interaction patterns of Warkop customers were interactions in the form of cooperation, competition, conflict, accommodation and assimilation that occurred at certain times, and each form of interaction could be in the form of interactions between individuals and individuals, groups and groups. groups and form a lifestyle and community. The driving factor for mutual interaction with fellow customers and fellow Warkop owners in this study is that imitation in this case mimics the desires of other customers in terms of taste, identification and motivation while the penghamabt factor is sometimes a suspicion towards other warkop and other customers. The positive impact of Warkop is as a place to drink coffee for coffee lovers, a place to relax, a place to eliminate boredom by utilizing existing facilities. The negative impact is the lack of awareness of managing time. Both of these impacts on average have become a lifestyle for some people in Sinjai